RESPONSE ON THE PHYSICAL FUNCTION AND ANTHROPOMETRY OF LUNG TB PATIENTS BY REGULAR THERAPY AND FOOD INTERVENTION: A PRELIMINARY RESEARCH - Setiawan, Budhi; Ernawati, Ernawati; Suprapti, Herni (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2014)
Patients with active lung tuberculosis (TB) have low body mass index (BMI) because of a wasting. Changes in body weight during the initial period of TB therapy correlated with the death risk, illness severity and relapse as well as decrease of patients physical function. This study aimed to measure the effectiveness of soybean supplementation among TB patients with standard therapy in improving physical function and nutritional status. Fifty nine patients were randomly divided into two groups.Intervention group received one hundred fifty gram nutritional supplementation and control group did not receive anything. Both groups were on the same regular antituberculosis treatment. Assessment of outcomes were done twice, before supplementation and then after 1 month of the treatment. There were significant differences in the changes in proxy physical function parameter in the control and treatment group (3.16 ± 0.83 vs. 4.50 ± 1.47, P < 0.05) and changes in nutritional status variable (0.33 ± 0.15 vs. 0.47 ± 0.16, p < 0.05). However there was no significant difference in the change in mid upper arm circumference (0.83 ± 0.31 vs. 0.93 ± 0.31, p > 0.05). Further research is needed to confirm this result.